From Innocence to Terror: The Role of Children in the 2018 Surabaya Church Bombing - Mandela, Aprison; Josias Simon Runturambi, Arthur; Hanita, Margaretha; Syauqillah, Muhamad; Ayu Permatasari, Diah (Jurnal Keamanan Nasional, 2024)
Terrorism has experienced the development of the actors involved in it. Children are targets and new actors are being targeted to become cadres by terrorists, specifically by the Islamic State of Iraq and Syria (ISIS). The May 13, 2018, incident, the suicide bombing that occurred in Surabaya, East Java, involved four children as perpetrators. Four children who are siblings named Fadhil, Firman, Fadhila, and Famela have succeeded in creating public concern which creates a feeling of insecurity. This paper aims to analyze efforts to involve children as terrorist actors in the 2018 Surabaya Bombing case. The method used is a descriptive qualitative research method. Researchers collect primary data through interviews and secondary data from journals, books, and other writings on related issues. The results of this study found that the involvement of children as perpetrators of terror could occur after the child passed the six steps of the ladder for someone to become a terrorist by Fathali Moghaddam. The use of children as terrorists is due to several considerations, ranging from low cost, being able to attract media attention to being effective in physically touching targets.